ANALISIS EFEKTIVITAS PELAKSANAAN SISTEM PENGELOLAAN LIMBAH MEDIS PADAT DI PUSKESMAS PANTE RAYA TAHUN 2024 - Tiara, Helda; Alamsyah, Sanjaya; Zulfikar (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT This study aims to analyze the management of solid medical waste at Puskesmas Pante Raya using a descriptive qualitative approach. This method is used to provide a detailed description of the ongoing medical waste management conditions at the health center. The results show that while most processes, such as waste segregation, packaging, and temporary storage, have been carried out in accordance with established standards, there are several deficiencies that need to be addressed. Key findings include the absence of a consistent self-weighing system to record the amount of waste and the manual transportation process being conducted without a specialized trolley, which increases the risk of contamination. Additionally, the duration of waste storage in the temporary storage area often exceeds the stipulated limit of 90 days. Although there is cooperation with third parties for final waste management, there are frequent delays in the transportation process. This study concludes that improvements in the recording system and adherence to transportation schedules are necessary to reduce the risk of waste accumulation and ensure more effective medical waste management at Puskesmas Pante Raya. Keywords : Solid Medical Waste, Waste Management